SISTEM PENDAFTARAN TANAH YANG MEMBERIKAN KEPASTIAN HUKUM HAK ATAS TANAH - Rahayu Subekti; Purwono Sungkowo Raharjo; Hadhika Afghani Imansyah (Jurnal Komunikasi Hukum, 2022)
The purpose of writing this journal is to provide analysis and research on a land registration system that provides legal certainty of land rights for owners of land rights. Whereas for legal certainty which is a manifestation of the Safe Principle, a positive publication system is needed that is supported by the role of village officials. This Positive Publication System will later protect legal subjects written in the land book complete with floor plans in order to avoid land dispute conflicts. However, in the event of a dispute, in this positive publication system, the legal subject whose name is listed in the land book even though they are not entitled to the land will still be protected while the injured party will be given compensation in other forms. Here the role of Pamong Desa is needed, in addition to assisting the community, but based on PP no. 24 of 1997, it has a task, one of which is to provide legal protection and certainty to land rights holders as well as to collect data on ownership of rights in the apartment system. This is certainly related to the Obligation of Land Owners to Report their Land Ownership to the Village so that it is properly inventoried as an asset used, not as an absentee item.